Key informants’ perceptions of telehealth palliative care for people living with dementia in nursing homes - Joan G. Carpenter; Laura C. Hanson; George Demiris; Nancy Hodgson; Mary Ersek (BMC Geriatrics)
Abstract Background Studies have shown that palliative care delivered to people living with dementia (PLWD) in nursing homes (NHs) improves care quality and reduces potentially burdensome treatments. However, access to palliative care services in NHs is uncommon. Telehealth may extend the reach of specialty palliative care consultation, yet strategies for feasible and acceptable NH implementation remain unknown. During implementation of an embedded pragmatic pilot clinical trial for PLWD, we aimed to describe key informants’ perceptions of a NH telehealth palliative care intervention. Methods Guided by the Practical Implementation Sustainability Model (PRISM), we engaged key informants in 30–60-minute focus groups and individual semi-structured interviews to understand barriers and facilitators to implementation of a NH telehealth palliative care intervention in one NH. Interview prompts addressed contextual factors that influenced outcomes. Interviews were conducted and recorded via videoconference, transcribed, and analyzed using the Reach, Effectiveness, Adoption, Implementation, and Maintenance (RE-AIM) framework. Results Participants (n = 14) included NH administrators and other leaders, palliative care providers, telehealth representatives, dementia advocates, a care partner, and a PLWD. Identified barriers to implementation included stigma surrounding dementia, palliative care, and NHs; multiple logistical pieces required to implement the intervention; inflexibility of palliative care providers to meet NH needs; and inability to assess residents in person. Facilitators included convenient, user-friendly and readily available telehealth equipment, and NH staff presence during visits. Outcomes most relevant to the key informants were increased goals of care conversations, improved symptom management and quality of life, and decreased health care utilization. Suggested adaptations included increased family engagement in the logistics of the intervention and strong NH advocacy. Conclusions In this study, key informants provided feedback that barriers to implementing NH telehealth palliative care far outweighed the facilitators for uptake. Future work will focus on employing NH staff in user centered design to overcome barriers such as optimal timing for consults and/or scheduled consult days to fit NH workflow, assessing organizational readiness for implementing change, and identifying dementia-specific and palliative care education needs.